Key Factors to Promote a Vulnerable Region as a Competitive Tourist Destination - MARÍN-IDÁRRAGA, Diego; SÁNCHEZ-TORRES, Juan; SANABRIA-RANGEL, Pedro (Journal of Environmental Management and Tourism, 2023)
The aim of this research was to identify the key factors to promote a vulnerable region as a competitive tourist destination. Using Dwyer and Kim´s model as a reference, this was an exploratory research based on a confirmatory factor analysis. The results show that created resources, tourist destination management, situational conditions, competitive performance related to visitors, and competitive performance related to governmental support are determining factors to promote the region as a competitive tourist destination. From the theoretical point of view, it contributes to demonstrate that, although the competitiveness of tourist destinations is a complex and multidimensional phenomenon, it is possible to define a reduced number of factors on which competitiveness performance falls. From the practical point of view, this work offers a relevant input to direct public policies in matters of tourism in a vulnerable region. This research is an exploratory and confirmatory factor analysis.